Benefits of social vs. non-social feedback on learning and generosity. Results from the Tipping Game - Colombo, Matteo; Stankevicius, Aistis; Seriès, Peggy (Frontiers in Psychology, 2014)
Although much work has recently been directed at understanding social decision-making, relatively little is known about how different types of feedback impact adaptive changes in social behavior. To address this issue quantitatively, we designed a novel associative learning task called the “Tipping Game,” in which participants had to learn a social norm of tipping in restaurants. Participants were found to make more generous decisions from reward feedback in the form of facial expressions, in comparison to reward feedback in the form of symbols such as ticks and crosses. Furthermore, more participants displayed learning in the condition where they received social reward feedback than participants in the non-social condition. Modeling results showed that the pattern of performance displayed by participants receiving social reward feedback could be explained by a lower sensitivity to economic costs.